1996
DOI: 10.1007/s004360050111
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile of the liver of mice infected with cysticerci of Taenia crassiceps

Abstract: Proton nuclear magnetic resonance (NMR) spectra of liver extracts from mice infected with cysticerci of Taenia crassiceps for 84 or 200 days showed differences in the concentrations of liver metabolites as compared with those of normal liver. The livers of mice infected for 84 days contained less glycogen and β-hydroxybutyrate but more glycine, taurine, betaine, phosphocholine (PC), choline, alanine and lactate. At 200 days post-infection (p.i.) the levels of hepatic glycogen and β-hydroxybutyrate remained low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…With the reduction in the amount of FA found in the liver of infected animals, it can be assumed that FAs are no longer available in excess to be channelled into ketogenic processes. The lower concentration of hepatic b-hydroxybutyrate in mice infected with T. crassiceps (Corbin et al, 1996) supports this hypothesis. It seems then that the FAs available in the liver were used for energy generation; continued complete oxidation of FA is essential for this organ as it derives most of its energy from this process (Seifter & Englard, 1994).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…With the reduction in the amount of FA found in the liver of infected animals, it can be assumed that FAs are no longer available in excess to be channelled into ketogenic processes. The lower concentration of hepatic b-hydroxybutyrate in mice infected with T. crassiceps (Corbin et al, 1996) supports this hypothesis. It seems then that the FAs available in the liver were used for energy generation; continued complete oxidation of FA is essential for this organ as it derives most of its energy from this process (Seifter & Englard, 1994).…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the removal of FAs, the cysticerci also acquire substantial amounts of glucose from the host. In response, the liver attempts to correct this metabolic disturbance by mobilizing glycogen stores and accelerating the gluconeogenic process (Corbin et al, 1996(Corbin et al, , 1999. As a consequence, the utilization of glucose in secondary pathways, such as FA synthesis, is inhibited (Goodridge et al, 1986;Katz, 1986;Sugden et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these authors demonstrated a 200-fold increase of 17 b-oestradiol, involving a feminization of T. crassicepsinfected male mice. The cysticerci of T. crassiceps could also be involved in the disruption of mouse food intake (Crompton et al 1985;Corbin et al 1996;2000), as well as affecting the immunological system of the mouse host (Huerta et al 1992;Terrazas et al 1994Terrazas et al , 1999Villa and Kuhn 1996;Toenjes et al 1999). Under these circumstances, it was not surprising that T. crassiceps infection led to modification of the antagonistic behaviour and dominance status of male mice.…”
Section: Discussionmentioning
confidence: 96%
“…The parasite transmission mode, lethality of the infection, and the life history traits are decided by the parasites (Poulin et al, 2011). Even when the parasite is in sub-lethal level, it can cause damage to the host by taking partial control over the behaviour such as changes in locomotion, light sensitivity, pain threshold, disruption of food intake, even affecting the immunological system of the host (Holmes and Bethel, 1972; Crompton et al, 1985; Huerta et al, 1992; Poulin, 1994; Thompson and Kavaliers, 1994; Corbin et al, 1996; Kavaliers et al, 1999). The parasitic infections in aquatic birds are one of the major threats to their populations along with factors including human disturbances at the nesting sites and wetlands, deforestation (Subramanya, 2006; Taher, 2007), hunting (Talukdar, 1999), and poaching of eggs and chicks (Talukdar, 1999; Chandrasekhar, 2009).…”
Section: Discussionmentioning
confidence: 99%